2018
DOI: 10.2340/00015555-2872
|View full text |Cite
|
Sign up to set email alerts
|

Blood Predictive Biomarkers for Nivolumab in Advanced Melanoma

Abstract: Nivolumab response rate is 40% in metastatic melanoma. Few studies have evaluated pre-treatment biomarkers predictive of response. The aim of this study was to identify potential peripheral blood biomarkers associated with survival in patients with advanced melanoma treated with nivolumab. All advanced melanoma cases treated with anti-programmed cell death protein 1 (anti-PD1) over a 3-year period in the Dermato-Oncology Department, Nantes, France were identified. For each case, 9 potential blood biomarkers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 16 publications
3
44
0
Order By: Relevance
“…40 With the recent developments in cancer immunotherapy, NLR is a potential tool for predicting tumor response to treatment. 41,42 Our study has some limitations inherent to its retrospective nature. This is a single-center study and follow-up was relatively short for some patients.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…40 With the recent developments in cancer immunotherapy, NLR is a potential tool for predicting tumor response to treatment. 41,42 Our study has some limitations inherent to its retrospective nature. This is a single-center study and follow-up was relatively short for some patients.…”
Section: Resultsmentioning
confidence: 97%
“…This information may provide a scientific basis to alter treatment and follow‐up, that is, once a subgroup of worse prognosis is identified among patients with same stage disease, it would be worthwhile offering a closer follow‐up or make modifications in the neoadjuvant/adjuvant therapies . With the recent developments in cancer immunotherapy, NLR is a potential tool for predicting tumor response to treatment …”
Section: Discussionmentioning
confidence: 99%
“…For ipilimumab-treated melanoma patients, high baseline NLR was associated with shorter PFS and OS ( 46 , 48 ). For PD1ab treatment, high baseline NLR was linked to non-response ( 50 ) and to worse OS for melanoma ( 49 , 79 ) and for several other types of cancer being investigated in phase I studies with PD1ab/PD-L1ab treatment ( 79 ). For example, NLR was associated with lower incidence of response, poor PFS, and OS for NSCLC ( 71 , 80 ) and for RCC ( 81 ).…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…A decrease in CD11c + CD14 + CD16 + HLA-DR hi monocytes, accompanied by a significant increase in overall survival (OS), has been observed in recurrent glioblastoma after post-surgery Pembrolizumab, but only in patients that had also received neo-adjuvant anti-PD-1 immunotherapy before surgery ( 53 ). Chasseuil et al reported a statistically significant decrease in OS in relation to an increase in the total monocytic fraction in pre-treatment blood samples from advanced melanoma patients treated with Nivolumab, suggesting its potential as prognostic biomarker ( 54 ). In addition, in a cohort of NSCLC patients, the post-treatment AMC was higher in non-responders compared to responder patients, suggesting a predictive role of monocytes in anti-PD-1 therapy ( 27 ).…”
Section: Anti-pd-1 Inhibitorsmentioning
confidence: 99%